THE INFLUENCE OF TV ADVERTISEMENT AND PACKAGING TOWARD PURCHASE INTENTION OF WARDAH COSMETIC (BRAND AWARENESS AS MEDIATING VARIABLE) - Ayu, AYU TIARA B1021131091 (Jurnal Manajemen Update, 2017)
ABSTRACK : This research aims to determine the effect of the TV advertisement, packaging, and brand awareness towards purchase intention of Wardah Cosmetic in Pontianak. Thecontent analysis is used to analyses the terms and the subsequent understanding about TV advertisement, packaging,Â  brand awarenes, and purchase intention by detail. Previous research findings indicate that there are significant relationships between TV advertisement, packaging, and brand awareness to the purchase intention. Themethodology applied in this elaboration is path analysis.This result of this research shows thatÂ  for directly analysis there is a significant influence among brand awareness toward purchase intention while there is no significant influences among TV advertisment and packaging toward brand awareness. Although, for indirectly analysis the result shows that there is significant influences among TV advertisement and packaging toward purchase intention through brand awareness as mediator. This indicates the important roles of brand awareness in order to predict and increasing the consumer purchase intention of Wardah cosmetic in Pontianak. Keywords : TV advertsement, packaging, brand awareness, purchase intention